Hydrodynamic characterization of soil compaction using integrated electrical resistivity and X-ray computed tomography - Cimpoiasu, Mihai O; Kuras, Oliver; Wilkinson, Paul; Pridmore, Tony; Mooney, Sacha J (Vadose Zone Journal, 2021)
© 2020 The Authors. Vadose Zone Journal published by Wiley Periodicals LLC on behalf of Soil Science Society of America Modern agricultural practices can cause significant stress on soil, which ultimately has degrading effects, such as compaction. There is an urgent need for fast, noninvasive methods to characterize and monitor compaction and its impact on hydraulic processes. Electrical resistivity tomography (ERT) is a well-established method used for the assessment of soil hydraulic properties due to its high temporal resolution and sensitivity to changes in moisture content and salinity, whereas X-ray computed tomography (CT) can be used for high-spatial-resolution imaging of soil structure. We used the combined strengths of both methods to study soil under three different levels of compaction. The soils were X-ray scanned and electrically monitored after the application of a saline solution to the soil surface. The scans revealed the pore network architecture and allowed us to compute its size and connectivity. The ERT models revealed inhibited percolation rates for soils with a lower bulk density, but also how resistivity changes are spatiotemporally distributed within the soil columns. Furthermore, we obtained a quantitative link between the two methods, by which voxels more densely populated with pores were associated with higher temporal variations in electrical resistivity. Building on this, we established a spatial collocation between pore structure and distribution of solution during percolation. This demonstrates the potential of the combined strengths of the two tomographic methods to obtain an enhanced characterization of soil hydrodynamic properties.